Spline-approximation of estimates of correlation sequences of harmonic signals - Шутко, В. М. (Proceedings of National Aviation University (archive), 2002)
A least-squares spline processing of estimates of the correlation sequences of complex harmonic signals that contain a random component is proposed, taking into account the nonlinear analytical connection between the real and imaginary parts of these sequences.